Land, Liberty, and Water : Morelos After Zapata, 1920-1940 - Salinas, Salvador, 1981- (Book collections on Project MUSE., 2018)
"This book analyzes the aftermath of the Zapatista revolt in Morelos by providing a new political and environmental history of the state in the 1920s and 1930s"--Provided by publisher